Emperor of ruin - Wexler, Django (Wexler, Django. Burningblade & Silvereye, 2023)
"The last surviving Chosen, Ashok, has finally risen up and taken control of The Twilight Order. He promises equality and prosperity, but Gyre and Maya know the truth. Only death follows in Ashok's wake. To take him down, Gyre will have to unite old allies--from all across The Splinter Kingdoms and the depths of Deepfire. And Maya will have to seek out a legendary weapon hidden in the mountains that could turn the tide in their battle for freedom"--